Suffering and the remedy of art - Schweizer, Harold 1950- (State Univ. of New York Press, 1997)
This book suggests that a listening to suffering may profit from a literary hearing, and vice versa. It is not only that literature tells of suffering but that suffering may tell us something about the nature of literature